If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (x + 6)((2x + -1)(x + 6)) = 0 Reorder the terms: (6 + x)((2x + -1)(x + 6)) = 0 Reorder the terms: (6 + x)((-1 + 2x)(x + 6)) = 0 Reorder the terms: (6 + x)((-1 + 2x)(6 + x)) = 0 Multiply (-1 + 2x) * (6 + x) (6 + x)((-1(6 + x) + 2x * (6 + x))) = 0 (6 + x)(((6 * -1 + x * -1) + 2x * (6 + x))) = 0 (6 + x)(((-6 + -1x) + 2x * (6 + x))) = 0 (6 + x)((-6 + -1x + (6 * 2x + x * 2x))) = 0 (6 + x)((-6 + -1x + (12x + 2x2))) = 0 Combine like terms: -1x + 12x = 11x (6 + x)((-6 + 11x + 2x2)) = 0 Multiply (6 + x) * (-6 + 11x + 2x2) (6(-6 + 11x + 2x2) + x(-6 + 11x + 2x2)) = 0 ((-6 * 6 + 11x * 6 + 2x2 * 6) + x(-6 + 11x + 2x2)) = 0 ((-36 + 66x + 12x2) + x(-6 + 11x + 2x2)) = 0 (-36 + 66x + 12x2 + (-6 * x + 11x * x + 2x2 * x)) = 0 (-36 + 66x + 12x2 + (-6x + 11x2 + 2x3)) = 0 Reorder the terms: (-36 + 66x + -6x + 12x2 + 11x2 + 2x3) = 0 Combine like terms: 66x + -6x = 60x (-36 + 60x + 12x2 + 11x2 + 2x3) = 0 Combine like terms: 12x2 + 11x2 = 23x2 (-36 + 60x + 23x2 + 2x3) = 0 Solving -36 + 60x + 23x2 + 2x3 = 0 Solving for variable 'x'. The solution to this equation could not be determined.
| (3b-4)(6b+5)-2= | | x=4/3×3.14×7^3 | | -14a+9=11a+12 | | 4/7=2c | | 2n+b-3n=-6 | | f(x)=(x^2-3x-1)/x | | R^2-9/2r=29 | | 0=-16t^2+10t+56 | | -25+3x=0 | | 20n-19n+21=-21 | | x=4/3×3.14×7×7×7 | | 1/x^2-4=0 | | 15x-177=6x-6 | | 4x+4=3y+6 | | Log[9]5+log[9]4= | | 7.3=(2x)/(.3-x) | | X/5=x-7/7 | | 3/17x=-6 | | 15x^4+6x^2-18x^3= | | n/-1.8=2.1 | | 7x+8=9-(4x-9) | | -16x^2+1000x+3=9 | | 4x+y=225 | | -3=4w | | 3y-6=21x | | 7j+14=16 | | z=20*x | | X^1/2-8=0 | | 2x-2+6x-10=180 | | 4x+6=7x+12 | | 2-8(3-6x)=0 | | 4(x-3)=3-(x+5) |